2009
DOI: 10.1177/000348940911801210
|View full text |Cite
|
Sign up to set email alerts
|

Local Neurotoxins for Prevention of Laryngeal Synkinesis after Recurrent Laryngeal Nerve Injury

Abstract: Low-dose VNC injections appear to be relatively safe and effective in selectively inhibiting spontaneous aberrant reinnervation after RLN injury in an animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…With unilateral UVFP, to prevent or counteract synkinesis, either the total number of axons innervating the adductor muscles must be increased, or the number of aberrant nerve fibers innervating the abductor muscle (posterior cricoarytenoid [PCA] muscle) must be reduced. As a neurotoxic agent, vincristine has been shown to inhibit neural regeneration in a rat post‐traumatic nerve injury model . In another rat study, we found paclitaxel to be equally as effective as vincristine for preventing reinnervation of a denervated muscle …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…With unilateral UVFP, to prevent or counteract synkinesis, either the total number of axons innervating the adductor muscles must be increased, or the number of aberrant nerve fibers innervating the abductor muscle (posterior cricoarytenoid [PCA] muscle) must be reduced. As a neurotoxic agent, vincristine has been shown to inhibit neural regeneration in a rat post‐traumatic nerve injury model . In another rat study, we found paclitaxel to be equally as effective as vincristine for preventing reinnervation of a denervated muscle …”
Section: Introductionmentioning
confidence: 76%
“…Vincristine administration in the setting of chemotherapy has been associated with toxicity including neutropenia, neuropathy, and a small therapeutic window . Although low‐dose administration of vincristine following vocal fold paralysis may avoid toxicity and achieve the desired effects, paclitaxel provides an alternative with a possibly wider therapeutic index . Additionally, prior studies have demonstrated that paclitaxel and vincristine have no effect after reinnervation has occurred .…”
Section: Discussionmentioning
confidence: 99%
“…Selective prevention of reinnervation of a specific muscle following a nerve injury was originally conceived as a way to reduce laryngeal synkinesis . Other clinical applications are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Yian et al showed that vincristine prevented facial nerve recovery into a target muscle after a transection injury with primary neurorrhaphy, which may have led to enhanced reinnervation of adjacent muscle groups as well as a reduction in synkinetic muscle activity . Studies by McRae et al in a rat larynx model, and by Paniello in a canine larynx model, both confirmed that vincristine is effective in blocking neural regeneration when administered to the posterior cricoarytenoid muscle.…”
Section: Introductionmentioning
confidence: 94%
“…{8} McRae et al independently confirmed that vincristine effectively blocked reinnervation in a rat RLN injury model. {9}…”
Section: Introductionmentioning
confidence: 99%